2013
DOI: 10.1002/humu.22257
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Complex III Deficiency Caused by a HomozygousUQCRC2Mutation Presenting with Neonatal-Onset Recurrent Metabolic Decompensation

Abstract: Mitochondrial complex III (CIII) deficiency is a relatively rare disease with high clinical and genetic heterogeneity. CIII comprises 11 subunits encoded by one mitochondrial and 10 nuclear genes. Abnormalities of the nuclear genes such as BCS1L and TTC19 encoding mitochondrial assembly factors are well known, but an explanation of the majority of CIII deficiency remains elusive. Here, we report three patients from a consanguineous Mexican family presenting with neonatal onset of hypoglycemia, lactic acidosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 17 publications
3
61
0
Order By: Relevance
“…These findings suggested UQCRC2 might function as a key protein downstream of CDH18. UQCRC2 is one of the two core proteins of the ubiquinol-cytochrome c reductase complex (complex III), which constitutes a part of the mitochondrial respiratory chain [28,29]. It was recently reported that homozygous missense mutation in UQCRC2 might cause mitochondrial complex III deficiency, which is a relatively rare disease [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested UQCRC2 might function as a key protein downstream of CDH18. UQCRC2 is one of the two core proteins of the ubiquinol-cytochrome c reductase complex (complex III), which constitutes a part of the mitochondrial respiratory chain [28,29]. It was recently reported that homozygous missense mutation in UQCRC2 might cause mitochondrial complex III deficiency, which is a relatively rare disease [28].…”
Section: Discussionmentioning
confidence: 99%
“…UQCRC2 is one of the two core proteins of the ubiquinol-cytochrome c reductase complex (complex III), which constitutes a part of the mitochondrial respiratory chain [28,29]. It was recently reported that homozygous missense mutation in UQCRC2 might cause mitochondrial complex III deficiency, which is a relatively rare disease [28]. Putignani et al observed that the content of UQCRC2 in breast cancer cell was significantly decreased compared to that in normal epithelial cells [30,31], which is in accordance with our findings on gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…CLPP mutations lead to Perrault syndrome, which is a heterogeneous autosomal recessive condition characterized by sensorineural hearing loss and ovarian failure 148 . Finally, mutations in the gene encoding the pseudo-mitoprotease UQCRC2 cause a recurrent metabolic decompensation with neonatal onset 149 , whereas XPNPEP3 mutations result in a severe nephropathy 150 .…”
Section: Mitoproteases and Human Diseasesmentioning
confidence: 99%
“…They are caused by mutations in catalytic and structural subunits as well as in assembly factors [5-10]. So far, the vast majority of mutations leading to complex III deficiency have been localized to the nuclear BCS1L gene, which encodes a mitochondrial inner membrane translocase necessary for the import and insertion of the RISP subunit into complex III [11].…”
Section: Introductionmentioning
confidence: 99%